2006
DOI: 10.1002/anie.200503915
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Proteins in Membranes of Living Cells by High‐Resolution Scanning Ion Conductance Microscopy

Abstract: Do not touch! The surface of a living cell is soft and responsive and therefore high‐resolution imaging of the cell membrane has not been possible to date. Now noncontact imaging of protein complexes in the plasma membrane of living cells has been demonstrated (see picture) and has been used to follow the cells' structural reorganization. This breakthrough opens up a wealth of new experiments in membrane and cell biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
187
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(193 citation statements)
references
References 22 publications
3
187
1
2
Order By: Relevance
“…Evidently, the hopping-mode scanning algorithm (defined briefly above; also see Materials and Methods) is able to visualize the structures clearly. Indeed, the topographical features of boar spermatozoon and PC12 revealed by SECM are very similar to those previously obtained with SICM (15,34), which is regarded highly as an ultrahigh-resolution in situ imaging technique. Further evidence for the powerful nature of the SECM technique comes from the fact that the neurite and varicosity, which administrate neuron transduction and axon formation, of PC12 cells were visualized much more clearly compared with a previous SECM report using more conventional imaging protocols (14).…”
Section: Resultssupporting
confidence: 82%
“…Evidently, the hopping-mode scanning algorithm (defined briefly above; also see Materials and Methods) is able to visualize the structures clearly. Indeed, the topographical features of boar spermatozoon and PC12 revealed by SECM are very similar to those previously obtained with SICM (15,34), which is regarded highly as an ultrahigh-resolution in situ imaging technique. Further evidence for the powerful nature of the SECM technique comes from the fact that the neurite and varicosity, which administrate neuron transduction and axon formation, of PC12 cells were visualized much more clearly compared with a previous SECM report using more conventional imaging protocols (14).…”
Section: Resultssupporting
confidence: 82%
“…The work discussed herein [40][41][42]44,87], and studies performed in other groups [47,101] has demonstrated that SICM can be used to provide information about the polarity and magnitude of substrate charge. In fact, SICM is sensitive to substrate surface charge for similar tip-substrate distances to which the standard SICM response is observed, approximately one tip diameter away from the surface [55,99]. The response of the ionic current upon approach to a charged interface differs significantly from that to an uncharged surface, with the response depending on the magnitude and sign of the applied bias, the nanopipette characteristics (geometry, charge) and ionic strength of the bulk solution [40,41,47].…”
Section: (Iii) Surface-induced Rectificationmentioning
confidence: 93%
“…Therefore, SICM can capture topographic images without any tip-sample contact. Although high spatial resolution (~6 nm) has been reported for SICM (Shevchuk et al 2006), it cannot be attained routinely. The spatial resolution is approximately equal to the diameter of the pipette opening, when the tip end-sample separation is similar to the diameter of the pipette opening.…”
Section: Non-contact Imagingmentioning
confidence: 99%